1998
DOI: 10.1074/jbc.273.10.5963
|View full text |Cite
|
Sign up to set email alerts
|

Fission Yeast Mitotic Regulator Dsk1 Is an SR Protein-specific Kinase

Abstract: Intricate interplay may exist between pre-mRNA splicing and the cell division cycle, and fission yeast Dsk1 appears to play a role in such a connection. Previous genetic analyses have implicated Dsk1 in the regulation of chromosome segregation at the metaphase/anaphase transition. Yet, its protein sequence suggests that Dsk1 may function as a kinase specific for SR proteins, a family of pre-mRNA splicing factors containing arginine-serine repeats. Using an in vitro system with purified components, we showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 47 publications
4
44
0
Order By: Relevance
“…For this purpose, a large number of crosses were done between mis3-224 and various mutants implicated in DNA replication, RNA metabolism, cell cycle control and other cellular aspects (see Experimental procedures). We found that mis3-224 was synthetic lethal with two mutations involved in RNA metabolism, namely, dsk1 null (Takeuchi & Yanagida 1993;Tang et al 1998) and cold-sensitive (cs) dis3-54 mutant (Kinoshita et al 1991). Tetrad dissection indicated that the mis3-224 dsk1 null double mutant failed to grow at any temperature.…”
Section: Functional Overlapping Of Mis3 With Dsk1 Dis3 and Pp1mentioning
confidence: 95%
“…For this purpose, a large number of crosses were done between mis3-224 and various mutants implicated in DNA replication, RNA metabolism, cell cycle control and other cellular aspects (see Experimental procedures). We found that mis3-224 was synthetic lethal with two mutations involved in RNA metabolism, namely, dsk1 null (Takeuchi & Yanagida 1993;Tang et al 1998) and cold-sensitive (cs) dis3-54 mutant (Kinoshita et al 1991). Tetrad dissection indicated that the mis3-224 dsk1 null double mutant failed to grow at any temperature.…”
Section: Functional Overlapping Of Mis3 With Dsk1 Dis3 and Pp1mentioning
confidence: 95%
“…Srp2 contains two short SR\RS repeat elements (SR1 and SR2) flanking an arginine-rich region (Figure 1), which is necessary for targeting the protein to the nucleus. The srp2 + gene is essential for cell viability, and its second RBD and the two SR elements are required for its function in i o. SR proteinspecific kinases are conserved in fission yeast [26,29]. Dis1-suppression kinase (Dsk1) protein, originally described as a mitotic regulator [30], displays high activity in phosphorylating S. pombe Srp1 and Srp2 proteins in itro and is a functional homologue of human SRPK1 based on complementation assay in i o.…”
Section: Figure 1 Structural Domains Of Fission Yeast Srp1 and Srp2 Pmentioning
confidence: 99%
“…Plasmids pET-28bGST, pET-28adsk1 + , pET-28bGST-prp2 + , pET-28asrp1 + , pET-28bGST-srp1 + , pET-28bsrp2 + and pET28bGST-srp2 + have been described previously [26,29]. Recombinant proteins, GST-Srp1, Srp1, GST-Srp2, Srp2, GST-pre-RNA processing 2 (Prp2) and Dsk1, were expressed in the Escherichia coli strain BL21(DE3)pLysS, and the relative amounts of recombinant proteins in lysates were estimated as described previously [26,29].…”
Section: Plasmids and Protein Productionmentioning
confidence: 99%
See 2 more Smart Citations